Online game pioneers at work : interviews with some of the top online game pioneers of our times - Ramsay, Morgan (Apress, 2015)
From the foreword written by Richard Bartle, the coauthor of MUD: ""They [the 16 people interviewed in the book] tell things just the way they are, without any spin, and with insights freely flowing. That's either a feature of successful game developers or a testament to Morgan's interviewing skills. I suspect it's a combination of both."" In this groundbreaking collection of 15 interviews, successful founders of entertainment software companies reflect on their challenges and how they survived. You will learn of the strategies, the sacrifices, the long hours, the commitment, and the dedi.